The first global financial crisis of the 21st century,Part II: Introduction - Reinhart, Carmen; Felton, Andrew (2009)
Sadly, our previous compilation of VoxEU columns, ‘The First Global Financial Crisis of the 21st Century,’ was not the last word on the subject. Since the publication of that volume in June 2008, the global crisis has both deepened and widened. The industrial world has seen the largest bank failures in its history, and many governments have intervened in the financial system in a manner that would once have been unthinkable. Wall Street and the City of London, along with most other financial centers, have been changed forever. Many storied financial firms have failed or been merged away, and others are left with significant ownership positions of national governments. The economy of Iceland has suffered a collapse just as sizable as any of Latin America or East Asia during the last few decades. Vox authors have kept up their prolific pace of commenting on unfolding events. In keeping with the mission of Vox, columnists both applied existing economic research to understand events and pointed the way to new avenues for research. These articles, it has to be understood, were written ‘in the moment’ over the past six months and so incorporate to a varying extend the history we have lived through. To help place individual contributions within this historical sequence, an appendix updates the timeline of events from our June publication through December.